Nilai-Nilai Pendidikan Islam Dalam Serial Animasi Riko The Series Karya Teuku Wisnu - Muhammad Ghozali (Oasis : Jurnal Ilmiah Kajian Islam, 2023)
One of the children's film series that shows the lives of children with the spectacle of Islamic character values, namely the animated series Riko by Teuku Wisnu, in this film teaches children to understand Islamic knowledge which is so simple that it is easy to understand, then many things attract children's attention. children to learn and invite their imagination along with the intellectual development of children, especially early childhood. The purpose of this research is to find out and be able to give ibrah and understand the urgency contained in the animated series Riko the series by Teuku Wisnu. This study uses library research with a descriptive approach to content analysis methods. The data collection technique uses documentation on Riko's animated shows through seeing, understanding, living and telling scene by scene in the film. The results of this study are that there are Islamic educational values by summarizing and observing the dialogue in Riko's animated episode, namely the value of faith, worship value, and moral value. The values contained are important to be implemented in children's activities, especially to always carry out orders and stay away from Allah's prohibitions, always put their trust and not do mazmumah traits such as arrogant, envious, and so on